Sustainable development? Zimbabwean wildlife conservancies, state crisis, the rise, promise and failure of community based ecotourism development lessons for the Southern African Development Community (SADC) - Muzvidziwa, Victor N. (Cultural Research Publishers, 2016)
The aim of this paper is not just to inform readers about another case of failed development in Africa. The strength of the paper lies in its attempt to examine how the various actors have responded and are strategising and finding ways to deal with the economic crisis that has impacted negatively on the well being of conservancies in Zimbabwe. While the focus is on Zimbabwe's conservancies a regional focus is pursued since study has implications far beyond a single country. Discussions throughout the paper use the Southern African Development Community(SADC) region as its backdrop. Zimbabwe is renowned for its abundance of wildlife natural resources....